2019
DOI: 10.21203/rs.2.12385/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KARAOKE: Krill oil versus placebo in the treatment of knee osteoarthritis: protocol for a randomised controlled trial

Abstract: Background : Knee osteoarthritis (OA) is a common and important cause of pain and disability, but

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Other studies [ 19 , 25 ] also confirmed that krill oil had the ability to reduce C-reactive protein levels, which are the markers of systemic inflammation. Oxidative stress and inflammation are the main cause of knee osteoarthritis (OA) pathogenesis and krill oil could not only ameliorate knee pain [ 26 ] but also reduce systemic inflammation of the body caused by OA [ 27 ]. In terms of inflammatory bowel disease (IBD), ω-3 PUFA and astaxanthin in KO also show the significantly anti-inflammatory property in the management with promising results [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies [ 19 , 25 ] also confirmed that krill oil had the ability to reduce C-reactive protein levels, which are the markers of systemic inflammation. Oxidative stress and inflammation are the main cause of knee osteoarthritis (OA) pathogenesis and krill oil could not only ameliorate knee pain [ 26 ] but also reduce systemic inflammation of the body caused by OA [ 27 ]. In terms of inflammatory bowel disease (IBD), ω-3 PUFA and astaxanthin in KO also show the significantly anti-inflammatory property in the management with promising results [ 28 ].…”
Section: Introductionmentioning
confidence: 99%